Determinasi Permintaan Produk Halal Lokal sebagai Manifestasi Gerakan Boikot Global: Analisis Efek Substitusi dalam Perspektif Teori Permintaan Islam - Muhammad Fakhri Nasir Assujai; Mia Jumiati; Juniarsih Juniarsih; Ramadhani Irma Tripalupi (CV. Kalimasada Group, 2026)
The global boycott movement triggered by geopolitical conflicts has significantly influenced Muslim consumer behavior, leading to increased demand for local halal products. This phenomenon cannot be fully explained by conventional demand theory, as it overlooks the influence of religious values and Islamic ethical principles on consumption decisions. This study aims to analyze the determinants of demand for local halal products as a manifestation of the global boycott movement and to explain the substitution effect from the perspective of Islamic demand theory. A qualitative conceptual approach was employed using a Systematic Literature Review (SLR), synthesizing scholarly literature on Muslim consumer behavior, Islamic economics, substitution effects, and global boycott movements. The findings reveal that demand for local halal products is driven by intrinsic religiosity, collective identity, ethical and geopolitical awareness, trust in halal certification, and competitive price and quality. The substitution effect is shaped not only by economic considerations but also by the Islamic principles of halal, maslahah (public benefit), and the utility of obedience, which together form consumers' spiritual rationality. The study concludes that Islamic demand theory provides a more comprehensive explanation of Muslim consumption behavior than conventional demand theory. These findings imply that strengthening the halal industry requires policies that reinforce halal certification, promote Sharia consumer literacy, and enhance the competitiveness of local halal products to foster a sustainable halal economic ecosystem.